2017
DOI: 10.1136/acupmed-2016-011180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture at St25 and Bl25 in a Sennae-induced rat model of diarrhoea-predominant irritable bowel syndrome

Abstract: EA at ST25 and/or BL25 had a positive effect on objective markers of diarrhoea in a IBS-D rat model and induced changes in EC cell number, colonic TPH and 5-HT contents. The effects of EA stimulation at ST25/BL25 on IBS-D rats may be mediated by excitation of sympathetic nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Besides, other studies have also uncovered the mechanism of action of acupuncture in treating IBS-D, and experimental data show that electroacupuncture at Zusanli can also inhibit the vimentin protein expression level to adjust the gastrointestinal motility [52]. Additionally, the antidiarrheal effect has been connected to the regulation of the excitation of sympathetic nerves, which in turn will reduce the number of enterochromaffin cells (ECs), colonic tryptophan hydroxylase (TPH) expression, and 5-HT content in feces and colonic tissues in IBS-D rats [53]. Furthermore, Liu et al had stimulated the Zusanli and Shangjuxu acupoints to lower the level of spinal N-methyl-D-aspartic acid (NMDA) receptor NR2B subunit in IBS rats, so as to counter the visceral sensitivity [54].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, other studies have also uncovered the mechanism of action of acupuncture in treating IBS-D, and experimental data show that electroacupuncture at Zusanli can also inhibit the vimentin protein expression level to adjust the gastrointestinal motility [52]. Additionally, the antidiarrheal effect has been connected to the regulation of the excitation of sympathetic nerves, which in turn will reduce the number of enterochromaffin cells (ECs), colonic tryptophan hydroxylase (TPH) expression, and 5-HT content in feces and colonic tissues in IBS-D rats [53]. Furthermore, Liu et al had stimulated the Zusanli and Shangjuxu acupoints to lower the level of spinal N-methyl-D-aspartic acid (NMDA) receptor NR2B subunit in IBS rats, so as to counter the visceral sensitivity [54].…”
Section: Discussionmentioning
confidence: 99%
“…Stainless steel disposable acupuncture needles (0.16 × 7 mm, Zhong Yan Tai He Medical Instrument Co., Ltd., Beijing) were inserted at ST25 and ST37 to a depth of 4-5 mm and at SP6 and LR3 to a depth of 2-3 mm and connected to an EA apparatus (HANS-200A, Nanjing, China). Electrical stimulation was applied in the form of disperse-dense waves at alternating 2 Hz and 15 Hz frequencies, respectively, and 1 mA intensity for 15 min [8, 19, 20]. Other animals received only 15 min of restraint stress.…”
Section: Methodsmentioning
confidence: 99%
“…A considerable number of studies found that acupuncture can improve gastrointestinal motility, decrease intestinal permeability, and reduce visceral hypersensitivity [7, 8]. Our previous polycentric randomized controlled trial showed that EA is effective against IBS and is superior to loperamide in relieving anxiety [9].…”
Section: Introductionmentioning
confidence: 99%
“…An evolutionary Fontana-Masson staining was used for EC cell counting [ 33 ]. Briefly, the colonic sections were deparaffinized and rehydrated for Fontana-Masson staining (ab150669, Abcam, UK).…”
Section: Methodsmentioning
confidence: 99%